Dampak Media Sosial Terhadap Munculnya Gerakan Radikalisme : Sebuah Sistematika Review - Anggraeni, Wilfrida Charismanur (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2022)
This study aims to find out how the issue and understanding of radicalism spread through social media, where technological developments by the current of globalization are one of the causes of the rampant growth of radicalism through social media and to find out bibliometric analysis of the theme of radicalism. This research uses Scopus data in 2016-2021 which will show concept mapping and clustering related to the theme of radicalism. Then the data was collected through the Scopus database search using the keyword radicalism, where this research focused on cluster analysis, dominant topics, related themes, and mapping of radicalism study topics based on the number of articles whose visualization seemed dominant and analyzed using VOSviewer software. The results of this study indicate that the topic of radicalism has four dominant keywords that often appear, namely Politic, Country, History, Terrorism. So that these four topics become the focus for the majority of writers who want to study the topic of radicaism. This research contributes to the development and mapping of studies of radicalism as one of the problems in security both nationally and internationally, but this research has limited data that is only analyzed based on Scopus so it does not have comparative data.